Work Environment, Work Motivation, and Employee Performance: Evidence from PT BSB (Bangun Semangat Bersama) - Farhan Thaha Giffari; Cecep Haryoto (Paradoks : Jurnal Ilmu Ekonomi, 2026)
This study aims to analyze the influence of work environment and work motivation on employee performance at PT Bangun Semangat Bersama. Employee performance was positioned as the dependent variable, while work environment and work motivation served as the independent variables. The research employed a quantitative associative design. Primary data were collected through questionnaires distributed to 100 employees and analyzed using multiple linear regression with SPSS. The results indicate that work environment has a positive and statistically significant effect on employee performance (t = 13.518; p < 0.001). Work motivation also demonstrates a positive and significant impact (t = 15.158; p < 0.001). Simultaneously, both work environment and work motivation significantly affect employee performance (F = 283.584; p < 0.001). The coefficient of determination (R² = 0.854) shows that work environment and work motivation collectively explain 85.4% of the variance in employee performance, while the remaining 14.6% is influenced by other variables not examined in this study. These findings suggest that PT BSB should maintain a safe, comfortable, and supportive work environment while continuously enhancing employee motivation through appropriate incentives and engagement strategies to achieve higher performance levels.